Non-Moslem Consumers Perception Toward Purchasing Halal Food Product - Hana Meka Madinah; Indarini Indarini; Dudi Anandya (Journal of Entrepreneurship and Business, 2020)
This thesis aims to analyze how Non-Muslim consumers' perceptions of purchasing halal food products. This type of research is Basic research with causal objectives and uses a quantitative research approach. This study also uses a purposive sampling approach which is a sampling technique based on the aim of getting samples from people who have met established criteria. The analysis in this study was SEM (Structural Equation Modeling) which processed data using SPSS 20 and AMOS 18 software. This software was used for testing the Measurement Model and Structural Model. The results of this study stated that the attitude, subjective norm and perceived behavioral control of non-Muslim consumers in Surabaya had a positive influence on the purchase intention of halal food products. Thus providing opportunities for businessproducts to expand its reach by selling halal food products. Keywords: Attitude, Subjective Norm, Perceived Behavioral Control, Purchase Intention, Halal Product, Halal Food